Oncolytic vaccinia virus armed with anti-CD47 nanobody elicit potent antitumor effects on multiple tumor models via enhancing innate and adoptive immunity - Jie Chen; Liu Yang; Mengyuan Li; Qian Ye; Shibing Wang; Zengpeng Li; Wenbin Qian (Journal for ImmunoTherapy of Cancer)
Objective Targeting CD47 for cancer immunotherapy has been studied in many clinical trials for the treatment of patients with advanced tumors. However, this therapeutic approach is often hampered by on-target side effects, physical barriers, and immunosuppressive tumor microenvironment (TME).Methods To improve therapeutic efficacy while minimizing toxicities, we engineered an oncolytic vaccinia virus (OVV) encoding an anti-CD47 nanobody (OVV-αCD47nb). We demonstrated the specific binding activity of αCD47nb secreted from the virus-infected cells to CD47 and that both secreted αCD47nb and OVV-αCD47nb blocked the “don’t eat me” signal of macrophages.Results Intratumorally injected OVV-αCD47nb continuously releases the αCD47nb in tumor tissues, thereby conferring superior systemic activity against breast and colon tumor cells and prolonging survival compared with OVV control. Furthermore, treatment with OVV-αCD47nb also remodeled the TME, as shown by increased T cell infiltration, CD8+ T cell activation and tumor-associated macrophages polarization, significantly enhancing innate and adoptive immunity. Additionally, the inclusion of programmed cell death protein-1 inhibiting boosted the anticancer efficacy of OVV-αCD47nb and raised the full response rate in tumor-bearing animals.Conclusion Overall, our findings highlight the therapeutic potential of OVV-αCD47nb for breast and colon cancer, and demonstrate its ability to modulate the immune cell profiles within tumors. This has established a rationale for further exploring OVV-αCD47nb as a potential therapy in the clinic.